Exploring maths 7 : home book home book - Straker, Anita; Fisher, Tony., Hyde, Rosalyn., Jennings, Sue., Longstaffe, Jonathan (Great Britain, Scotprint : Pearson Longman, 2009)
its about the powers and roots, functions and graph, equations and formula, 2D and 3D shapes
Keywords: Fractions -- Mathematics., Probabilities -- Mathematics -- Mathematics